O niektorých praslovanských základoch hydronym z juhozápadného Slovenska (Malý Dunaj a Dudváh) - Hladký, Juraj (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
Refering to the oldest hydronymia from Southwestern Slovakia which is the oldest Slavic state, we provide the examples of the old Slavic lexical layer fund. These appellative vocabulary is undifferentiated (or only minimally differentiated) in Slovak dialects, but also in the Slavic languages. In earlier documents and hydronymical material we also find the old petrified vocabulary that could gradually change its original semantic structure in the Slavic languages (or in Slovak language). There are also the examples of the elements of appellative vocabulary. In the process of development of Slavic base these linguistic units could gradually pass and become a part of the vocabulary of the so called edge of the language; they could lose or modify its phonetic form. The author analyzes the proper names from Žitný ostrov (Rye Island) (between the Danube River and the Little Danube), which is considered Slovakia–Hungary, and from the immediate surroundings. Preliminary analysis shows that the names of the rivers in this area are of domestic (Slovak) origin, the historically younger names of marshes and wetlands are instead of Hungarian origin.